2017
DOI: 10.1590/s1679-87592017133706502
|View full text |Cite
|
Sign up to set email alerts
|

Wave run-up on embayed beaches. Study case: Itapocorói Bay, Southern Brazil

Abstract: This paper presents a new approach for estimating run-up on embayed beaches based on a study of the microtidal coast of Itapocorói Bay, Southern Brazil using the surf similarity parameter and wave height at break location. The four step methodology involved: 1) direct wave measurement (34 days), wave run-up measurement (19 days at 7 points within the bay), measurement of bathymetry and beach topography in the entire bay; 2) tests on available formulae to calculate wave run-up; 3) use of the SWAN spectral wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Indeed, comparing several empirical formulations Atkinson et al [23] showed that the most accurate models give a relative error of R 2% of up to 25%. Thus, it is often necessary to develop site-specific runup formulations [25,26], which require a significant measurement effort to cover a wide range of oceanographic conditions at a given site [25]. Furthermore, it is often hazardous to collect data in natural environments, especially during extremely energetic events [10,27], which is probably the reason for the sparse existence of runup data from extreme events.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, comparing several empirical formulations Atkinson et al [23] showed that the most accurate models give a relative error of R 2% of up to 25%. Thus, it is often necessary to develop site-specific runup formulations [25,26], which require a significant measurement effort to cover a wide range of oceanographic conditions at a given site [25]. Furthermore, it is often hazardous to collect data in natural environments, especially during extremely energetic events [10,27], which is probably the reason for the sparse existence of runup data from extreme events.…”
Section: Introductionmentioning
confidence: 99%
“…Vieira da Silva et al (2016) showed that for a protected stretch of coast where only diffracted waves are present, despite their reduced heights, the unidirectional oblique waves are the main forcing responsible for sediment transport. Bonetti et al (2012) and Vieira da Silva et al (2017) demonstrated the importance of using wave parameters after they have undergone nearshore refraction and attenuation for estimating wave run-up on embayed beaches. Harley et al (2017) and Mortlock et al (2017) demonstrated the importance of wave direction on beach erosion by analysing an Australian East Coast Low (ECL) storm event that impacted Sydney, Australia in 2016.…”
mentioning
confidence: 99%
“…Whilst these results are pragmatic and efficient in modeling reality, they are difficult to generalize because they are usually calibrated to a certain condition. Several studies constructed empirical formulae which are only suited for certain bottom topographies [11]- [15]. A numerical model, on the other hand, is undoubtedly applicable in a variety of situations.…”
Section: Introductionmentioning
confidence: 99%